AN ELECTROCHEMICAL STUDY OF THE COBALT ELECTRODEPOSITION ONTO A CARBON FIBER ULTRAMICROELECTRODE - Luis Humberto Mendoza-Huizar; Jair A. Corona-Castro; Giaan A. Álvarez-Romero; Margarita Rivera; Clara H. Rios-Reyes; L.E. Bañuelos-García; E. García-Sánchez (Journal of the Chilean Chemical Society, 2022)
A kinetic study of the cobalt electrodeposition onto carbon fiber ultramicroelectrodes of 11 µm of diameter from an aqueous solution containing CoCl2 0.01 M + NH4Cl 0.1 M was conducted at overpotential conditions. From the voltamperometric studies, it was found that the value of the diffusion coefficient is 1.2x10-5 cm2 s-1. The analysis of the current density transients indicates the existence of a 3D nucleation and growth process. Also, it was observed that the values of the number of active nucleation sites increases as the value of the applied potential decreases.